Menumbuhkan jiwa wirausaha generasi muda di era pandemi dengan memanfaatkan teknologi digital - Siyamto, Yudi (Nur Science Institute, 2022)
This community service activity aims to foster entrepreneurial spirits in creating business opportunities without financial capital in the hope of providing benefits to the surrounding community in the form of financial or non-financial benefits. This community service activity method uses the lecture method, discussion-presentation, by resource persons to participants and is closed with a question and answer session. The results of community service activities in Tamantirto village have a positive impact, where there is an active interaction in the form of a symbiotic mutualism between academics, in this case, lecturers, and the local community. So that it can provide information and an overview to the community and feel helped by inputs from academics, socialization of entrepreneurial empowerment raises awareness and an entrepreneurial spirit in the community to be ready to compete in this era of accelerating science and technology, which can later be applied by participants and transmitted to the broader community.